2020
DOI: 10.1002/fsn3.1891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different drying temperatures on the rehydration of the fruiting bodies of Yu Muer (Auricularia cornea) and screening of browning inhibitors

Abstract: cornea cv. Yu Muer) is a new white variety of edible fungus that was selected from a mutant of Auricularia cornea by the Engineering Research Center of the Ministry of Education, Jilin Agricultural University. Yu Muer is in genus Auricularia, family Auriculariaceae, order Auriculariales, class Agaricomycetes, and phylum Basidiomycota. It is an edible fungus and is also used in medicine (Royse, 2014; Wang, Jiang, et al., 2019a; Wang, Li, et al., 2019b). The fruiting bodies of Yu Muer are thick, tender, and cris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…for other dried fruits. A similar tendency to generate 5-HMF at high temperature has been reported for HAD of Yu Muer fruit (Chen, Lv, et al, 2020); and the browning index and 5-HMF concentration of dried papaya were found to be positively correlated with processing temperature (Udomkun et al, 2015).…”
Section: Internal Browningsupporting
confidence: 79%
See 3 more Smart Citations
“…for other dried fruits. A similar tendency to generate 5-HMF at high temperature has been reported for HAD of Yu Muer fruit (Chen, Lv, et al, 2020); and the browning index and 5-HMF concentration of dried papaya were found to be positively correlated with processing temperature (Udomkun et al, 2015).…”
Section: Internal Browningsupporting
confidence: 79%
“…In addition, the decrease in DR was related to the transfer of moisture. As the drying proceeds, the area of moisture evaporation gradually moved from the outer layer of the sample to the inside, which extended the path of later moisture transfer, resulting in a gradual decrease in DR (Chen, Lv, et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fresh L. edodes have a short storage time and shelf life owing to their high enzymatic activity and water content (Chen, Lv, et al., 2020 ). The browning reactions specifically limit the shelf life to within a few days, with polyphenol oxidase (PPO) and peroxidase (POD) being the primary enzymes responsible for the enzymatic browning process (Singh et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%